2017
DOI: 10.1111/aen.12273
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic reclassification and genitalic morphology of the small water strider genusNesidoveliaAndersen & Weir and allied Microveliinae (Hemiptera:Veliidae)

Abstract: Phylogenetic analyses of the Australasian Microveliinae is given, including a reanalysis of Andersen and Weir (2003) dataset and an analysis of a new dataset of 46 morphological characters and 42 taxa. Analyses focused on pregenital, genital and postgenital structures of males and females, including putative male grasping and female antigrasping structures. Phylogenetic analyses resulted in a redefinition of the genus Nesidovelia Andersen & Weir, with Microvelia (Austromicrovelia) and Microvelia (Barbivelia) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Sexual conflict, specifically sexual coercion, may drive the striking morphological modification and dimorphism [ 21 , 34 , 48 , 49 ]. For example, it is believed that copulatory struggles have driven the evolution of male grasping structures to overcome female resistance in water striders and relatives [ 27 , 33 , 34 , 50 , 51 ]. The new fossils exhibit conspicuous sexual dimorphism in the protibia: (1) the protibia is slightly curved in males ( figure 2 b,d ; electronic supplementary material, figure S4 b,c ), whereas in females, the protibia is straight ( figure 2 e ; electronic supplementary material, figure S2 a ); (2) the protibia of males is armed with 15–17 discontinuous clusters of pegs along the innermost edge, consisting of 2–12 in each cluster ( figure 2 b–d ; electronic supplementary material, figures S2 c,d and S4 b,c ), forming a comb-like structure that is absent in females ( figure 2 e ; electronic supplementary material, figure S2 a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual conflict, specifically sexual coercion, may drive the striking morphological modification and dimorphism [ 21 , 34 , 48 , 49 ]. For example, it is believed that copulatory struggles have driven the evolution of male grasping structures to overcome female resistance in water striders and relatives [ 27 , 33 , 34 , 50 , 51 ]. The new fossils exhibit conspicuous sexual dimorphism in the protibia: (1) the protibia is slightly curved in males ( figure 2 b,d ; electronic supplementary material, figure S4 b,c ), whereas in females, the protibia is straight ( figure 2 e ; electronic supplementary material, figure S2 a ); (2) the protibia of males is armed with 15–17 discontinuous clusters of pegs along the innermost edge, consisting of 2–12 in each cluster ( figure 2 b–d ; electronic supplementary material, figures S2 c,d and S4 b,c ), forming a comb-like structure that is absent in females ( figure 2 e ; electronic supplementary material, figure S2 a ).…”
Section: Discussionmentioning
confidence: 99%
“…Various specialized grasping traits, including modified pregenital abdominal segments and external genital structures [27,50,[52][53][54], equipped and thickened profemora [2,27,32], and highly specialized antennae and hind legs that form clamps [2,33], have evolved in male gerrid species primarily for grasping and fighting during mating. In the related 'Veliidae', males commonly possess protibial combs as a clasping device [2,34,51]. The primary difference in protibial combs between the new fossil and most 'Veliidae' is that the pegs are continuously distributed in the latter.…”
Section: (B) the Sexual Conflict In The Evolution Of Water Stridersmentioning
confidence: 99%
“…Recently, some studies have reported secondary sexual traits, mating behavior, and sexual dimorphism in Veliidae, the sister family of Gerridae (e.g. Cassis et al 2018;Toubiana & Khila 2019). As there are only a few studies related to the reproductive ecology of Veliidae, it is not completely understood.…”
Section: Introductionmentioning
confidence: 99%